2015
DOI: 10.3402/meo.v20.27921
|View full text |Cite
|
Sign up to set email alerts
|

Near peer teaching in medical curricula: integrating student teachers in pathology tutorials

Abstract: IntroductionDue to increased cognitive and social congruence with their tutees, near peer teachers (NPTs) may be capable of more effectively delivering course material. This study examines NPTs as pathology tutors alongside more traditional teachers (e.g., consultants and registrars) to explore their acceptability, effectiveness, and years of ‘distance’ between tutors and tutees.MethodIn total, 240 first- and second-year undergraduate medical students were taught set material in a pathology tutorial setting by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 11 publications
2
55
1
2
Order By: Relevance
“…One possible explanation is that the social and cognitive congruence existing between the learner and NPT is perceived to be more important for learning than academic pedigree. A previous study by Tayler et al suggests that the desire for a qualified educator varies according to the level of training (Tayler et al, ). In their study, first year medical students were more likely to want a qualified clinical tutor as opposed to a NPT, however, this opinion was reversed in the second year.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that the social and cognitive congruence existing between the learner and NPT is perceived to be more important for learning than academic pedigree. A previous study by Tayler et al suggests that the desire for a qualified educator varies according to the level of training (Tayler et al, ). In their study, first year medical students were more likely to want a qualified clinical tutor as opposed to a NPT, however, this opinion was reversed in the second year.…”
Section: Discussionmentioning
confidence: 99%
“…A near peer can be defined as a learner who is 1 year or more senior to another learner undertaking the same training . This has led to many medical schools formally endorsing near‐peer teaching into their undergraduate curricula . To the best of our knowledge, no studies have explored near‐peer simulation training in the context of the assessment and management of acutely unwell patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that PAL had positively perceived and actual effects on learning when the groups are instructor-formed and supervised, whether they are nursing [10] or medical students [11,12] . The outcomes of instructor-formed student groups did not significantly differ from those taught by teaching staff [13] , and students considered their peers to be more important to success in examination than experts [14] .…”
Section: Introductionmentioning
confidence: 75%